2020
DOI: 10.3390/nu12030709
|View full text |Cite
|
Sign up to set email alerts
|

Regardless of the Brewing Conditions, Various Types of Tea are a Source of Acetylcholinesterase Inhibitors

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized, among others, by abnormally low levels of the neurotransmitter acetylcholine in the brain. Acetylcholinesterase (AChE) plays a significant role in the process through hydrolysis of the acetylcholine neurotransmitter. Currently, the main method for treatment of AD at a symptomatic stage entails administration of AChE inhibitors to patients diagnosed with the disease. However, it is also possible to take certain steps to treat AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Further weaker AChE inhibiting zones were detected for valerian ( 8 ), Echinacea ( 10 ), grape pomace ( 15 ) and artichoke ( 17 ). Green tea [ 46 ], lemon balm [ 47 ], rosemary [ 48 ], yerba mate [ 49 ], meadowsweet [ 50 ], artichoke [ 44 ] and grape pomace [ 51 ] were reported to inhibit AChE, which confirms our profiling results. For Eschscholzia , no prominent AChE inhibition was observed for 14 isolated alkaloids [ 52 ]; however, using a simple methanol extraction of the plant-fortified extract in our study, an intense AChE inhibiting zone at hR F 84 (MP 1) and five weaker zones (MP 1/2) were observed.…”
Section: Resultssupporting
confidence: 85%
“…Further weaker AChE inhibiting zones were detected for valerian ( 8 ), Echinacea ( 10 ), grape pomace ( 15 ) and artichoke ( 17 ). Green tea [ 46 ], lemon balm [ 47 ], rosemary [ 48 ], yerba mate [ 49 ], meadowsweet [ 50 ], artichoke [ 44 ] and grape pomace [ 51 ] were reported to inhibit AChE, which confirms our profiling results. For Eschscholzia , no prominent AChE inhibition was observed for 14 isolated alkaloids [ 52 ]; however, using a simple methanol extraction of the plant-fortified extract in our study, an intense AChE inhibiting zone at hR F 84 (MP 1) and five weaker zones (MP 1/2) were observed.…”
Section: Resultssupporting
confidence: 85%
“…However, in most of the above stated studies collection of authenticated tea samples (mostly market collected tea samples), sample preparation protocols and sample extraction protocols are different from the present study. Further, none of the studies clearly specified the origin, grade, manufacturing technique, particle size, and elevation of the tea samples used [20][21][22][23] although pharmacological activities and the sensory properties of tea are shown to be varied with the above-mentioned factors [18,[26][27][28][29][30]. Thus, we hope comparison of results of the present study with previously reported studies is not that meaningful and appropriate.…”
Section: Discussionmentioning
confidence: 57%
“…This disease is characterized by the reduction of neurotransmitter acetylcholine [1][2][3]. Therefore, inhibitors of acetylcholinesterase are used as a prevalent therapeutic approach to enhance acetylcholine levels [4,6,10,34] [20] on AChE inhibitory activity of 14 different instant tea variants including black tea showed that tea as a rich source of cholinesterase inhibitors which may play a significant role in Alzheimer's disease treatment. However, concentrations used in the AChE assay are not clear to compare the activity with other published findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations